MENINGKATKAN PROSES PEMBELAJARAN TEMATIK MENGGUNAKAN MEDIA GAMBAR BERCERITA DI KELAS IV SEKOLAH DASAR - Randi Eka Putra; Apdoludin Apdoludin; Jaya Putra (LP3M Universitas Muhammadiyah Muara Bungo, 2022)
The problem in this research is the low learning process and learning outcomes of fourth grade students at SDN 118/II Candi and the research objective is to improve the process and learning outcomes of students. This research is a classroom action research, which consists of two cycles. Each cycle consists of planning activities, implementing sactions, observing and reflecting. Data collection techniques in this study were observation, tests and documentation. The research subjects were 1 educator and 19 students. The results of this study show the learning process of educators, the first cycle of meetings is 95%, the second cycle of teacher observations is 100%. Observation of students during the learning process cycle I 65%, said to have not been successful. Cycle II 85%, said to be successful. The learning outcomes of students who completed the first cycle were 11 people or 57%. In the second cycle which was completed 17 people or 89%, were declared successful. Based on the results of this study, it can be concluded that Picture Storytelling Media can improve the process and learning outcomes of students in class VI.